INTERNAL CONTROL SYSTEM IN ENHANCING THE CORPORATE GOVERNANCE IN LISTED INSURANCE COMPANIES IN NEPAL (Universitas Teknologi Muhammadiyah Jakarta (UTM Jakarta), 2022)
This study aims to show the role of internal control in enhancing the corporate governance of insurance companies in Nepal. To attain the study’s objectives, four independent variables risk assessment, monitoring and supervision, control environment, and internal audit have been considered as well three dependent variables independent directors, transparency, and responsibility are taken. A descriptive research design has been used in the study. Fifteen insurance companies in Nepal have been chosen using the convenience sampling technique. Primary data has been collected from the staff of insurance companies in Nepal. A total of 384 respondents’ information is used in the research. Descriptive and inferential statistics are used for data analysis using SPSS and Excel software. Based on the result of the analysis, it was found that risk assessment elements positively enhance the corporate governance elements of transparency and responsibility. Elements of monitoring and supervision have a positive role to enhance the independent directors and transparency but a negative role on responsibility. Likewise, a controlled environment enhances the independent directors in a positive direction. Internal audit positively enhances the independent directors but responsibility has been affected negatively. The success of corporate governance is affected by the internal control activities in insurance companies in Nepal.